2017
DOI: 10.1038/ncomms14097
|View full text |Cite
|
Sign up to set email alerts
|

Electrically tunable organic–inorganic hybrid polaritons with monolayer WS2

Abstract: Exciton-polaritons are quasiparticles consisting of a linear superposition of photonic and excitonic states, offering potential for nonlinear optical devices. The excitonic component of the polariton provides a finite Coulomb scattering cross section, such that the different types of exciton found in organic materials (Frenkel) and inorganic materials (Wannier-Mott) produce polaritons with different interparticle interaction strength. A hybrid polariton state with distinct excitons provides a potential technol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 28 publications
1
57
0
Order By: Relevance
“…We exploit such resonant interactions and the hybrid nature of polaritons to dramatically enhance optical nonlinearities in our system allowing demonstration of polariton lasing at 200 K. Furthermore, the advantage of the implemented electrical injection scheme is that it does not require the use of low mobility organic hole injection layers that typically limits device performance 35 . Instead, the present device relies on well-established GaAs technology to electrically inject carriers into inorganic part of the device 36 and uses strong coupling regime to efficiently transfer excitation from inorganic to organic semiconductor excitations, thus promising a new route to electrical injection of organic active medium.…”
Section: Discussionmentioning
confidence: 99%
“…We exploit such resonant interactions and the hybrid nature of polaritons to dramatically enhance optical nonlinearities in our system allowing demonstration of polariton lasing at 200 K. Furthermore, the advantage of the implemented electrical injection scheme is that it does not require the use of low mobility organic hole injection layers that typically limits device performance 35 . Instead, the present device relies on well-established GaAs technology to electrically inject carriers into inorganic part of the device 36 and uses strong coupling regime to efficiently transfer excitation from inorganic to organic semiconductor excitations, thus promising a new route to electrical injection of organic active medium.…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsically large exciton binding energy of 1L WS 2 is in favor of stable exciton–polariton at room temperature, which is superior to most counterparts based on conventional semiconductors in view of developing practical applications. Flatten et al have reported the exciton–polariton formation of 1L WS 2 ‐coupled open microcavity ( Figure ) and electrically tunable hybrid polaritons in a 1L WS 2 ‐dye embedded microcavity together with the large Rabi splitting and the mixed excitonic nature. Further investigation can be extended to the experimental exploration of the possible room‐temperature superfluidity, superconductivity, and low threshold polariton lasing, where the rich many body physics can be explored such as quantized vortices, quantum phases, and polaritonic coherence properties.…”
Section: Luminescence Beyond Fundamental Excitonic Emission Of 2d Ws2mentioning
confidence: 99%
“…e) Cavity length‐dependent transmission spectra of hybrid WS 2 ‐TDBC microcavity with gate voltages of −210 V (left) and 210 V (right), respectively. d,e) Reproduced with permission . Copyright 2017, Springer Nature.…”
Section: Far‐field Spectroscopy Studies Of Eps In Tmdsmentioning
confidence: 99%
“…Gate tuning has also been demonstrated in a variety of hybrid polaritons such as PEPs and hybrid organic‐inorganic EPs . In the former case, PEPs were generated by coupling excitons in MoS 2 with localized plasmon resonance modes in silver nanodisk arrays (device structure similar to that of Figure a).…”
Section: Far‐field Spectroscopy Studies Of Eps In Tmdsmentioning
confidence: 99%
See 1 more Smart Citation